GravidApp 2.0: aplicativo educacional para a prática da enfermagem obstétrica no ensino superior - AMORIM, Claudiane Santana Silveira (Universidade Federal do Pará, 2023)
This work focused on developing an educational application entitled GravidApp 2.0, which was designed to be a theoretical-practical support for students of the Obstetric Nursing (ON) discipline, offered by Magalhães Barata School of Nursing at the University of the State of Pará (EEMB/UEPA). The theoretical methodological foundation is based on the concepts and principles of Health Education, teaching practices in Nursing and the theoretical discipline of Obstetric Nursing, in addition to notions and debates on active methodologies and Educational Technologies (ET). This study was based on the development of five main methodological phases adapted from Instructional Design Model of Falkembach (2005). In the first, diagnosis of the intervention context, data survey made towards the UEPA context, the Nursing course and the ON discipline. In the second, the survey and analysis of reference applications, educational applications on obstetrics were mapped on the Play Store platform. The third phase was to create and prototype the educational product on the multiplatform Unity and with help and support of an interdisciplinary team of professor and students of the University Federal of Pará (UFPA). In the fourth stage, validation of the application content, the participants were 13 Nursing Specialist Judges (SJ), who evaluated the GravidApp 2.0 through a 30 itens questionnaire that was answered using the Likert Scale that basead the verification of the Contente Validation Index (CVI). Furthermore, SJ gave recommendations about the application’s usage and functionalities. In the last phase, the application was reviewed and finalized to make it available on Play Store. Among the results, the following stand out: (i) the development of a useful, innovative, creative and easily accessible application may enhance ON students’ learning. In addition, the application can be replicated beyond UEPA context; (ii) the educational product proved to be valuable in terms of its contents, reaching more than 90% of its IVC global percentage, presenting an excellent evaluation among the SJ; (iii) the contributions were important to the training and performance of the researchers involved in its development. In this perspective, GravidApp 2.0 has potential to make direct contributions to the production of Educational Technology in the area of ON in the Northern Region of Brazil, since it is an authorial technology that promotes teaching-learning and assistance to the future Nursing professionals, making them more engaged and qualified.